Parental Involvement in the Transition from Paediatric to Adult Care for Youth with Chronic Illness: A Scoping Review of the North American Literature - Bryn Badour; Amanda Bull; Abha A. Gupta; Raza M. Mirza; Christopher A. Klinger (International Journal of Pediatrics)
With medical advancements and improvements in medical technology, an increasing number of children with chronic conditions survive into adulthood. There is accordant growing interest toward supporting adolescents throughout the transition from paediatric to adult care. However, there is currently a paucity of research focusing on the role that these patients’ parents should play during and after the transition to adult care and if maintained parental involvement is beneficial during this transition within a North American context. Accordingly, this scoping review utilized Arksey and O’Malley’s five-step framework to consider parental roles during chronically ill children’s transition to adult care. APA PsycInfo, CINAHL, EMBASE, MEDLINE, ProQuest, and Scopus were searched alongside advanced Google searches. Thematic content analysis was conducted on 30 articles meeting the following inclusion criteria: (1) published in English between 2010 and 2022, (2) conducted in Canada or the United States, (3) considered adolescents with chronic conditions transitioning to adult care, (4) family being noted in the title or abstract, and (5) patient populations of study not being defined by delays in cognitive development, nor mental illness. Three themes emerged from the literature: the impacts of maintaining parental involvement during transition to adult care for patients, parents experiencing feeling loss of stability and support surrounding the transition of their child’s care, and significant nonmedical life events occurring for youths at the time of transition of care. Parents assuming supportive roles which change alongside their maturing child’s needs were reported as being beneficial to young peoples’ transition processes, while parents who hover over or micromanage their children during this time were found to hinder successful transitions. Ultimately, the majority of reviewed articles emphasized maintained parental involvement as having a net positive impact on adolescents’ transitions to adult care. As such, practice and policies should be structured to engage parents throughout the transition process to best support their chronically ill children during this time of change.